Combining real and virtual sensors for measuring interaction forces and moments acting on a robot - Buondonno, Gabriele; De Luca, Alessandro (Proceedings of the ... IEEE/RSJ International Conference on Intelligent Robots and Systems, 2016)
We address the problem of estimating an external wrench acting along the structure of a robot manipulator, together with the contact position where the external force is being applied. For this, we consider the combined use of a force/torque sensor mounted at the robot base and of a model-based virtual sensor. The virtual sensor is provided by the residual vector commonly used for collision detection and isolation in human-robot interaction. Integrating the two types of measurement tools provides an efficient way to estimate all unknown quantities, using also the recursive Newton-Euler algorithm for dynamic computations. Different operative conditions are considered, including the special cases of pointwise interaction (pure contact force), known contact location, and of a base sensor measuring only forces. We highlight also the conditions for a correct estimation to be fully virtual, i.e., without resorting to a force/torque sensor. Realistic simulations assess the estimation performance for a 7R robot in motion, subject to an unknown external force applied to an unknown location.